Determination of interlayer exchange fields acting on individual (Ga, Mn)As layers in (Ga, Mn)As/GaAs multilayers. (5th February 2015) - Chung, Sunjae; Lee, Sangyeop; Yoo, Taehee; Lee, Hakjoon; Lee, Sanghoon; Liu, Xinyu; Furdyna, Jacek
Abstract: Magnetoresistance in antiferromagnetically coupled GaMnAs/GaAs:Be multilayers exhibits a unique step feature caused by sequential flips of magnetization in individual GaMnAs layers. Hysteresis loops corresponding to such magnetization flips in specific layers were measured by adjusting the range of the field scan to where the flip occurs. Using the hysteresis shifts of such partial loops, we were able to obtain the strength of the interlayer exchange coupling exerted on a given GaMnAs layer by the rest of the multilayers. This also allowed us to quantitatively establish the magnitude of the coupling of each GaMnAs layer with its adjacent neighbors.